Pengaruh Model Pembelajaran Active Team Quiz Terhadap Hasil Belajar Siswa Mata Pelajaran Pendidikan Agama Islam Kelas Xi Sma Muhammadiyah 9 Sedayulawas Brondong - Maftuhah, Maftuhah (Jurnal Pendidikan Islam, 2023)
This study discusses the Effect of the Active Team Quiz Learning Model on Student Learning Outcomes of Class XI Islamic Religious Education Subjects of SMA Muhmaadiyah 9 Sedayulawas Brondong Student Year 2022/2023. In the background, students tend to be passive and not in accordance with what is expected, as well as teachers who still use conventional learning or teachers who are very dominating in the learning process, especially in PAI subjects. To address these problems, researchers are interested in using the Active Team Quiz Learning Model as the main model in the PAI learning process. The formulation of the problem behind the research is "Is there an influence of the Active Team Quiz learning model on the Learning Outcomes of Students in Islamic Religious Education class XI of SMA Muhammadiyah 9 Sedayulawas Brondong for the 2022/2023 academic year?". This study used a type of quantitative research. Using the Pre-Experiment design method with one group pretest-posttest design technique. Data collection techniques in the form of observations and tests with a sample of 31 students from class XI of SMA Muhammadiyah 9 Sedayulawas Brondong. The test used the Pearson Product Moment correlation which was calculated at 0.763 the number of respondents 31 with dk – 2 = 29 who obtained r table 0.367 at a significant level of 5%. So rcalculate r>table (0.763 0.355). This shows that H 0 is > rejected and H1 is accepted with an interpretation of the correlation coefficient assessment found at 0.60 – 0.799 which is included in the strong category. As for the significance test using the t test obtained the results of t count 6.3579 and t table 1.699 so that it can be concluded that t count t>table which means that H 0 is rejected and H1 is accepted. Thus, it can be concluded that there is a strong and significant influence of the Active Team Quiz learning model on student learning outcomes in class XI Islamic Religious Education (PAI) subjects of SMA Muhammadiyah 9 Sedayulawas Brondong for the 2022/2023 academic year.